(untitled) (Revista Ciência Agronômica, 2015)
The effect was evaluated of feed supplementation (0.0, 0.4, 0.8, and 1.2% of body weight) on the qualitative aspects of goat meat (moisture, ash, fat, protein, colouring using the CIE (L*, a* and b *) system, pH, cooking loss and shear force), and also on the sensory attributes of goat aroma, off-aroma, colour, texture, tenderness, flavour, off-flavour, juiciness and overall appearance. A total of 32 crossbred Anglo-Nubian goats were used, organised into randomised blocks and finished on a pasture of caatinga. There was a quadratic effect (p<0.05) on the levels of ash and protein, with a maximum of 1.06 and 20.44 g/100 g respectively. A positive linear affect (p<0.05) was seen on fat levels, with an increase of 0.52 g/100 g. There was a negative linear effect (p<0.05) on the qualitative parameters of cooking loss, shear force and L*, with decreases of 3.32%, 0.77 kgf/cm2 and 3.39 respectively, and a quadratic effect (p<0.05) on a*, with a maximum of 9.13. There was a quadratic effect (p<0.05) on the parameter b*, with a maximum of 8.12, while the pH was not affected, with an average of 5.57. The sensory attributes were not influenced (p>0.05) by feed supplementation, except for colour and general appearance. Feed supplementation at 0.8% of body weight provides an increase in ash, fat and protein levels associated with qualitative improvements in cooking loss, tenderness and colouring, with increases in the sensory attributes of colour and overall appearance.